Tracking the Genealogical Reasoning Reconstruction of Nahdlatul Ulama (NU) Fiqh: From ‘Social Fiqh’ to ‘Civilization Fiqh’ - Reza Fauzi Nazar; Mohammad Fahmi Abdul Hamid (Tashwirul Afkar, 2022)
Fiqh, or in another term were called as Islamic jurisprudence, are the conceptions which are required by the Muslims to organize their interests in all aspects of life, provide the basics of the system of worship, administration, commerce, politics, social, and civilization. This article aims to trace and elaborate on the term "Civilization Fiqh.," or known as “Fiqh Peradaban”. It was initiated by Nahdlatul Ulama (NU) towards its one-century birth. By exploring and unraveling the genealogy of substantive thinking on the countenance of NU Fiqh as the epistemological basis for the ideas of “Civilization Fiqh”. The library method is used in writing this article. This article uses a descriptive-analytic approach; it tries to explain in an analytical-consistent manner through rigorous reading to unravel the transmission of the NU Fiqh reasoning constructions to obtain a fresh and modern formulation of "Civilization Fiqh.” The results of the discussion of this article include 1) It needs reading and interpretation of the reasoning of the Pesantren tradition to redefine the Islamic scientific tradition, which is seen as less adaptive to the changing realities of the new world order but has not lost its identity by the currents of modernity; 2) NU needs to expand the discussion of “Civilization Fiqh” not only on political issues and the nation-state. This genealogically was carried about simultaneously by NU activists, academics, ulama, even PBNU itself (2000-2019). Issues related to human rights (labor fiqh), injustice, gender (women fiqh), extraordinary crime (anti-corruption fiqh), and environmental destruction (energy fiqh, waste management fiqh). So it is no exaggeration if “Civilization Fiqh" in the future can discuss the reality of 21st-century society: free economy, internet technology society of think, building the smallest nation element: family with counter-discourse which capture the trending issue of childfree, demography fiqh, etc.